PROBLEMS AND SOLUTIONS WATER SUPPLY OF THE POPULATION OF THE REPUBLIC OF UZBEKISTAN - A.D. Dauletbayev (Scholar Express Journals, 2023)
Development of sanitary norms, rules and hygiene standards aimed at ensuring public health and preventing non-communicable diseases and acute intestinal infections, especially among the population living in rural areas
Keywords: drinking water; small water supply and sanitation systems; prevention; acute intestinal infections